2018
DOI: 10.3389/fnut.2018.00099
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status and Quality of Life Determinants of a Group of Elderly People With Food Insecurity

Abstract: Background: A good functionality is appointed by the elderly as one of the most important factors for a good quality of life, since it is associated with independency and autonomy. Studies show that elderly with food insecurity have greater limitations in daily living activities (DLA) when compared to food security elderly. Moreover, food insecure elderly are 60% more likely to be diagnosed with depression. We aimed to investigate the potential determinants of functional status (HAQ) and quality of life (EQ-5D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Another important finding of our study is the higher onset of disability among older women compared to men. This is in line with earlier studies in developed countries that have documented that, women have greater prevalence of impairment in most of the health outcomes [ 12 , 50 52 ]. Recent population-based studies in India also reported that older women rate their health as poor more often than older men and have higher rates of functional difficulties [ 37 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another important finding of our study is the higher onset of disability among older women compared to men. This is in line with earlier studies in developed countries that have documented that, women have greater prevalence of impairment in most of the health outcomes [ 12 , 50 52 ]. Recent population-based studies in India also reported that older women rate their health as poor more often than older men and have higher rates of functional difficulties [ 37 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies in high, middle and low-income countries have shown that functional disability, quality of life, and chronic conditions were strongly associated with depressive symptoms in the past 12 months [ 7 10 ]. Functional disability has consistently been identified as a crucial stressor contributing to poor well-being and depression [ 11 15 ]. Similarly, research has found that measures of physical functioning especially the activities of daily living (ADL) or instrumental activities of daily living (IADL) are related to feelings of well-being and any failure to carry out those has been found to trigger mental illnesses among older people [ 16 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four out of five studies that involved older people were conducted in Portugal (Baptista et al , 2018; Fernandes et al , 2018; Ganhão-Arranhado et al , 2018; Maia et al , 2019b), in population samples aged > 60, ≥ 65, between 66 and 99 and between 50 and 90, respectively, the fifth study took place in Greece in a population sample aged between 60 and 93 years (Grammatikopoulou et al , 2019). Apart from one study (Baptista et al , 2018) that did not report data about food insecurity, the reported results of food insecurity levels in older adults in Portugal varied between 16.6 (Maia et al , 2019b) and 70% (Ganhão-Arranhado et al , 2018). In Greece, the levels of food insecurity in a sample of older participants were estimated at around 76.3% (Grammatikopoulou et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“… For simplicity reasons the studies by Shankar-Krishnan et al (2018), Esturk et al (2014), Endeweld et al (2018), Ganhao-Arranhado et al (2018), Laurence et al (2017), Theodoridis et al (2018), Grammatikopoulou et al (2019), Dalma et al (2018), Pilot et al (2014), Baptista et al (2018) and Zamora‐Sarabia et al (2019) are not presented in this table because the sample size is less than 500 participants…”
Section: Figurementioning
confidence: 99%